Risk of Venous Thromboembolism with Statins: Evidence Gathered via a Network Meta-analysis - Oğuzhan Birdal; Mehmet Saygı; Remziye Doğan; Ozan Tezen; Ali Karagöz; İbrahim Halil Tanboğa (Balkan Medical Journal, 2023)
Background: Anticoagulants are the mainstay of treatment for venous thromboembolism (VTE). Studies have shown conflicting results regarding statins ability to reduce the incidence of VTE. Aims: To perform a network meta-analysis to determine which lipid-lowering agent was more efficacious in and had more evidence regarding reducing the VTE risk. Study Design: Network meta-analysis of the randomized controlled trials (RCTs). Methods: RCTs that assessed the effectiveness and safety of statins or fibrates and compared them to a placebo or another statin were eligible for the study. The outcomes examined in the study were deep vein thrombosis, pulmonary embolism, and/or VTE. We conducted a comprehensive search of the Medline database from 1966 to February 2017, using specific search terms related to VTE and statins. Additionally, we screened, and cross-checked relevant systematic reviews and meta-analyses. We performed a network meta-analysis to compare the different lipid-lowering agents to each other and the placebo and their effectiveness. Results: Twenty-seven RCTs were included in the network meta-analysis (n = 137,940). Pairwise meta-analysis revealed a statistically significant lower incidence of VTE with statins than with placebos (0.79% vs 0.99%, respectively; risk ratios: 0.87, 0.77-0.98; p = 0.022). Rosuvastatin had the most favorable effect in reducing VTE risk than the other statins, fenofibrate, and placebo. Fenofibrate was ranked the worst drug choice, because it increased risk of VTE when compared with the other statins. Rosuvastatin was the best choice for reducing the VTE risk when compared with the placebo (OR: 0.56, 0.42-0.75), atorvastatin (OR: 0.64, 0.44-0.95), pravastatin (OR: 0.50, 0.34-0.74), simvastatin (OR: 0.60, 0.42-0.86) and fenofibrate (OR: 0.37, 0.25-0.56). Compared with a placebo, rosuvastatin reduced the VTE risk by around 45% and fenofibrate increased the risk by 65%. Conclusion: Rosuvastatin is significantly reduces the risk of VTE when compared with a placebo, other statin subtypes, and fibrate. Furthermore, fenofibrate increased the VTE risk when compared with a placebo and statins.